(Studi Deskriptif Mengenai Pelayanan Perusahaan Daerah Air Minum (PDAM) Tirta Bumi Wibawa Kepada Pelanggan Di Kota Sukabumi) - M. Sauki; Rinrin Nuraeni (Mimbar Administrasi Mandiri, 2023)
This study evaluates the services of the Regional Drinking Water Company (PDAM) Tirta Bumi Wibawa Kota Sukabumi by focusing on five dimensions of public service quality: Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence. The research method is qualitative with a descriptive approach, involving in-depth interviews with informants, and testing the validity of the data with the Credibility test. The results showed that the service of PDAM TBW Sukabumi City was generally good. However, there are shortcomings in the Empathy dimension related to communication and in the Physical Evidence dimension related to physical facilities. The conclusion of this study is that PDAM TBW in Sukabumi City performs well overall, but needs to improve aspects that are still less than optimal. Suggestions include increasing socialization through the PDAM's official social media for more accurate information and updating pipes to improve water flow and quality.